Exploring the Potential of Meyerozyma guilliermondii on Physiological Performances and Defense Response against Fusarium Crown Rot on Durum Wheat - Zayneb Kthiri; Maissa Ben Jabeur; Fadia Chairi; Camilo López-Cristoffanini; Marta López-Carbonell; Maria Dolores Serret; Jose Luis Araus; Chahine Karmous; Walid Hamada (Pathogens, 2021)
Coating seeds with bio-control agents is a potentially effective approach to reduce the usage of pesticides and fertilizers applied and protect the natural environment. This study evaluated the effect of seed coating with Meyerozyma guilliermondii, strain INAT (MT731365), on seed germination, plant growth and photosynthesis, and plant resistance against Fusarium culmorum, in durum wheat under controlled conditions. Compared to control plants, seed coating with M. guilliermondii promoted the wheat growth (shoot and roots length and biomass), and photosynthesis and transpiration traits (chlorophyll, ɸPSII, rates of photosynthesis and transpiration, etc.) together with higher nitrogen balance index (NBI) and lower flavonols and anthocyanins. At 21 days post infection with Fusarium, M. guilliermondii was found to reduce the disease incidence and the severity, with reduction rates reaching up to 31.2% and 30.4%, respectively, as well as to alleviate the disease damaging impact on photosynthesis and plant growth. This was associated with lower ABA, flavonols and anthocyanins, compared to infected control. A pivotal function of M. guilliermondii as an antagonist of F. culmorum and a growth promoter is discussed.